Isolation and identification of Streptococcus pneumoniae that causes Respiratory Diseases - Shaymaa Habbaib Hassan AL Jowrani; Hanaa Daaj Khalaf Al-Mozan (مجلة علوم ذي قار, 2025)
Streptococcus pneumoniae is one of the bacterial species that colonize the respiratory system, and it causes many respiratory diseases, including pneumonia. Sputum specimens were collected from 270 patients of all ages suffering from respiratory diseases at the Consultants Clinic for Respiratory and Chest Diseases, Al-Hussein Teaching Hospital, and Public Health Laboratory in Thi-Qar Governorate during the period from October 2024 to March 2025.The aim in this study is the isolation and identification of Streptococcus pneumoniae, and morphological and (conventional and advanced) biochemical tests were performed. Results showed that Streptococcus pneumoniae isolates that cause respiratory diseases were (3.72%). Streptococcus pneumoniae had high rates of resistance to some antibiotics.This study showed that vancomycin is the best to treat Streptococcus pneumoniae, but S. pneumoniae is characterized by high resistance to tetracycline.